The mechanism of terminological analysis of performance indexes of the integrated information system - Кунченко-Харченко, Валентина Іванівна (Technology audit and production reserves, 2015)
It was analyzed the problem of automatically determining time series element in the text flow for machine documents and selecting statistical and linguistic criteria, allowing precise aims of research, which is to create problems for parsing unit and formation of context rules. Software was developed as a result of the practical implementation of the formed parsing block of context rules. Testing of the software using text content control revealed that a mechanism of terminological analysis of performance indexes of the integrated information system performs all tasks assigned to it. The proposed mechanism of terminological analysis is reliable in terms of getting time series of the integrated system. The resulting application performances are clear of noise. Test results of the developed mechanism are more accurate than the previously obtained by other methods.